3D complex resistivity tomography on cylindrical models using EIDORS. Issue 5 (1st December 2013) - De Donno, Giorgio; Cardarelli, Ettore
ABSTRACT: Complex resistivity imaging is a relatively new geophysical technique, developed in the last few decades mainly for hydrogeological and environmental applications. The aim of this work is to present an EIDORS application of the 3D complex resistivity tomography on cylindrical laboratory models. EIDORS is an open‐source numerical environment developed with the aim of sharing data and promoting collaboration between groups working in these fields. In spite of being a well‐recognised software for forward modelling and inversion for medical tomographies, EIDORS still needs to be adapted for geophysical purposes. We discuss the role played by the mesh choice and the contact impedances on the accuracy of the finite‐element solution achieved by tetrahedral elements. When a 3D tomography is performed on a standard machine with limited local memory, the dual reconstruction can help to retain a sufficient accuracy without increasing the allocated memory. Although for medical applications on the human body a linear inversion can effectively represent the slight changes in resistivity magnitude, when a subsoil has to be investigated resistivity can vary substantially. Thus we develop an algorithm to add to the non‐linear inversion for complex resistivity data, through the integration of the EIDORS basic functions. The algorithm has been validated through four synthetic examples. The reconstructed models, having a growing degree of complexity, are similar to the true ones. We highlight the role played by phase and resolution to detect the anomalies. When the dipole length is enlarged and the embedded anomalies decrease in size, the reconstruction becomes more difficult. We show that EIDORS could act as a base code for tomographic inversion of frequency‐domain data (and also of time‐domain real‐valued data) for laboratory problems, because of its high flexibility and reliability reached by the forward and inversion routines.